In Gefahr und grösster Not bringt der Mittelweg den Tod (1974) & Der starke Ferdinand (1976) - Kluge, Alexander (München : Edition Filmmuseum, 2009)
In gefahr und grösster Not bringt der Mittelweg den Tod: A female prostitute and thief makes her way through Frankfurt am Main with a female GDR spy in 1974 during carnival time. Der starke Ferdinand: A fundamentalist of the security forces, the chief of plant security Rieche has more proficiency in his job than his superiors permit. He needs to somehow demonstrate that his position is valuable. ## In gefahr und grösster Not bringt der Mittelweg den Tod = In danger and in deep distress, the middleway spells certain death (86 min.) -- Biermann-Film (1974 ; 3 min.) -- Porträt einer Bewährung = Policeman’s lot (1964 ; 12 min.) -- Strongman Ferdinand (1976 ; 91 min.) -- Ich war Hitler’s Bodygaurd = I was Hitler’s bodyguard (1999 ; 45 min.).
Onderzoek KASK Professioneel (OFVP)
Duits gesproken, ondertitels in Engels, Frans, Russisch, Chinees en Spaans
film
Keywords: Kluge, Alexander